Metal-Organic Framework-Based Hierarchically Porous Materials: Synthesis and Applications - Cai, Guorui; Yan, Peng; Zhang, Liangliang; Zhou, Hong-Cai; Jiang, Hai-Long (Chemical reviews, 2021)
Metal-organic frameworks (MOFs) have been widely recognized as one of the most fascinating classes of materials from science and engineering perspectives, benefiting from their high porosity and well-defined and tailored structures and components at the atomic level. Although their intrinsic micropores endow size-selective capability and high surface area, etc., the narrow pores limit their applications toward diffusion-control and large-size species involved processes. In recent years, the construction of hierarchically porous MOFs (HP-MOFs), MOF-based hierarchically porous composites, and MOF-based hierarchically porous derivatives has captured widespread interest to extend the applications of conventional MOF-based materials. In this Review, the recent advances in the design, synthesis, and functional applications of MOF-based hierarchically porous materials are summarized. Their structural characters toward various applications, including catalysis, gas storage and separation, air filtration, sewage treatment, sensing and energy storage, have been demonstrated with typical reports. The comparison of HP-MOFs with traditional porous materials (e.g., zeolite, porous silica, carbons, metal oxides, and polymers), subsisting challenges, as well as future directions in this research field, are also indicated.